Evaluasi dan Pemodelan Proses Bisnis menggunakan Business Process Management Notation (BPMN) dan Quality Evaluation Framework (QEF) pada KITATATA - Haris Surya Wijayanto; Aditya Rachmadi; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Kitatata is an organization engaged in the creative industry located in Malang City. Kitatata moves with a background in design, branding, software and others. Kitata provides services to customers who need help regarding marketing or design of products from customers. But in the interview process that has been carried out there is indeed a delay and the achievement of targets from the company. There are projects that have been abandoned for quite a long time and have not been resolved. Responding to the above problems, it is necessary to do a modeling of business processes in KITATATA. The first step is to analyze KITATATA's business processes using Vertical abstraction, RACI Chart, Value shop, functional decomposition. Then business process modeling will be carried out using BPMN and simulate the BIZAGI Modeller. The model that is formed will be evaluated with the Quality Evaluation Framework method and then entered on the 5 Why Analysis to find out the problem of the process.